(untitled) (Journal of Pure and Applied Sciences (Science Forum), 2023)
This study constrains the origin of pyrite of the Gombe In-lier to either biogenic or abiogenic using the analytical techniques Scanning Electron Microscopy and Energy Dispersive X-ray Spectroscopy and stable sulfur isotopes studies. The stable isotope compositions are useful indicators of the pathways of both biogenic and abiogenic pyrite formation. Textural and compositional information preserved in sedimentary pyrite from sediment-hosted ore deposits has contributed to elucidate their environment of formation. Backscattered SEM images of pyrite samples of this study were compared with that of the Huitrin Formation, Neuquén Basin in Argentina which is Aptian in age together with that of the offshore core samples of the Captain sands of Western Moray Frith Basin, United Kingdom with an Aptian age, the Valanginian (Lower Cretaceous) Wealden group of the Wessex Basin in Dorset, United Kingdom, the Turonian Afowo Formation in the Dahomey Basin of Nigeria. Result showed that in all SEM images, micrographs indicate either euhedral or framboids pyrites. Their respective isotopes results (mean) were also compared. The isotope result places the samples of the Gombe inlier with strong evidence that they could either have an origin that is biogenic or abiogenic, with a positive δ34S values signifying a closed system sulfate reduction during the pyrite mineralization of the area and of low temperature mineralization.